Evaluation of sustainable forest management techniques for biomass production and carbon sequestration - Heriansyah, Ika (2014)
Tropical forests deliver all kind of ecosystem services to the society. Thus, increasing the value and sustainable use of forest ecosystems has significant economic implication while at the same time is an important step towards resource conservation and environmental protection. The implementation of sustainable forest management (SFM) will ensure that the goods and services derived from the forest meet present-day needs. At the same time secure the continuous availability and contribution to long-term development, which will equalize the production goals with the environmental and social ones. However, forest use and management practices in the past which were concentrated more on timber production rather than forest services resulted in a number of environmental problems, such as land degradation, loss of biodiversity and greenhouse gas emission. With respect to the shifting paradigm of forest management from timber-oriented to resource-based management, it stands to reason that the spirit to use the forest environmental services must be practically actualized and that carbon trade forms one of the promising potentials that need to be explored. To achieve this, we must be willing to conserve and manage the remaining forest resources on sustainable basis and to conduct extensive reforestation programmes in degraded lands. In the term of managing forest resources on sustainable basis, achieving SFM requires environmentally responsible logging, hence the growing interest in reduced impact logging (RIL) as an alternative strategy to promoting good forestry practices in the tropics be expected can continue to fullfil the functions of forest ecosystems. Many studies implies that reduced impact logging (RIL) techniques greatly reduced damage to trees in the residual stand and reduced the amount of ground area disturbed by machinery. However, data and information on the characteristics of logged over forest and the suitability of RIL technique in the tropical forest is lacking. For these reasons, the study on effectiveness of RIL at the operational level and its impact on residual forest stand has been evaluated based on damage level, disclosure area and production potential of residual forest stand related to sustainable yield (study 1). The study of effective RIL technique in natural forests was conducted in several forest concessionaires in Indonesian Borneo, with focus on characterizing of forest structure and composition at different logging intensity. Forest inventories for both pre-harvested and post-harvested inventories were conducted at 100 ha area of each different logging intensity which determined based on harvested limit diameter, i.e. 40 cm, 50 cm and combination 40 and 50 cm. Pre-harvest inventories were conducted for all trees categories (diameter of 20 cm up), then mapping of trees, planning of roads and skidtrails, and determine directional felling. After harvesting, post-harvest inventories were conducted to calculate damage level and area of disclosure. Residual trees and damage trees was counted and used it to evaluate the effective of RIL technique at different logging intensity. Logging with applied harvest diameter limit of 50 cm resulted better condition of residual trees in term of number and volume, environmental friendly with lower damaged level and disclosure area compare to higher logging intensity with applied harvest diameter limit of 40 cm and combination of 40 and 50 cm. Residual stand can be recovered at the age of 35 years under D limit of 40 cm in primary forest, while 22 years of logged-over forest was not recovered, then residual trees need longer rotation of 57.3 to 63.2 years to achieve sustainable yield. Since logging intensity greatly influence the effectiveness of RIL and stand density of residual trees was greatly influence to production potential, the number, limit diameter determination,distribution and crown condition of harvest trees as well as regulation of cutting cycle (rotation age) must be considered. Supervising and monitoring from government must also be done during logging operation to ensure that RIL technique applied on the right procedure, thus meet ecological and economical function of forest ecosystems. In the field of logging, it is important to use the suitable harvesting system which complies with the principles of SFM, and in term of conducting extensive reforestation programme on degraded lands, achieving SFM requires suitable silviculture techniques through forest improvement or interventions, such as rehabilitation and restoration. Generally, however, suitable silvicultural treatments in nursery level as well as in operational level are limited and site specific. Lack of field data has been a barrier to proceed for evaluation of effectiveness of silviculture treatment on productivity changes in tropical degraded forests. Reforestation program through reintroduce tree species lost, especially fast growing dipterocarp is implemented to curtail degraded lands, then the study is focused on Shorea leprosula as a promising species to be used for reforestation program and offers opportunities for enhancing carbon sink. Shorea leprosula is also as the dipterocarp family which make up most of the tropical forests of Southeast Asia that have been commercially logged for many years, then has suffered a massive population reduction mainly because of the rate of exploitation of its timber. Restoring degraded logged-over forest which is indicated by low soil fertility and organic matter due to imbalance nutrient cycle are of paramount importance as there has been increasing attention towards these forest as the sustainable use of these resources. Organic matter has been identified as a key attribute in numerous soil properties and processes and important for productivity, community structure and fertility in terrestrial ecosystems. However, the influence of organic matter on soil depends on amount, type and size of added organic materials. The study on application of organic material was conducted in nursery stage (study 2) to evaluate the different kind and application rate of organic materials on growth and biomass accumulation and to determine suitable application for restoration of degraded forest in the humid tropics of Peninsular Malaysia. Mineral soils from degraded lands were amended with different rates of organic materials, such as pulp mill sludge, compost, oil palm mesocarp and their combinations and application rate were 0, ⅓, ½, ⅔, and ¾ of v/v. Growth measurement was conducted in every month for early growth up to 3 months after application and continued for every three months, while biomass were measured on initial, 3-, 6- and 12-month after application by destructive sampling method. Plant growth and biomass accumulation was increased by all amendments, however applied sludge with application rate 67% and more will be raising mortality rate. Growth rate of Shorea leprosula increased with decreasing application rate of mix organic materials, consequently.Based on this study, restoration program in tropical degraded forest without applied organic material indicated poor growth rate and biomass accumulation, then organic material application to be one of the requirement treatments needed for better results. Compost as well as the type of past forest structure were important factors which resulted best growth performance with high survival rate and recommended for restorationtechnique in Tekai Forest Reserve, Pahang, Malaysia and other comparative areas. The study suggest that to successful restoration program, preliminary study in nursery stage have to be done first to assist the recovery of an ecosystem that is damaged, degraded, or destroyed. Forest rehabilitation through forest plantations establishment serves to sequester large amount of carbon and are being consider as one of the reforestation options in order to reduce the increasing costs of wood from natural forests and also to decrease the pressure on remaining natural forests. Although the plantation has a potential of high productivity, it may have low yields and degrade the site if managed poorly. However, data and information on the factors that control the productivity of plantation and on ways of managing the site to maintain the productivity of successive tree crop are insufficient. Thus, the study on the effect planting design of multi-storied forest rehabilitation (study 3) and planting system (study 4) on productivity and biomass accumulation have been evaluate in order to meet the future demand of general utility timber and to combat global warming. Multi-storied forest management (MSFM) is a promising rehabilitation technique to promote forest development and management in the tropics. MSFM was established in Chikus Forest Reserve, Perak in 1992 to convert marginally poor forest into forest plantations in order to meet the future demand of general utility timber and to combat global warming. The experimental plots were set up to demonstrate five different planting designs, namely type A; one row of indigenous high quality timber species planted (Shorea leprosula) and one row of 3 years old exotic trees retained (Acacia mangium), 1:1, type B; 2:2, type C; 4:4, type D; 8:8 and type E; 16:16 in two different planting directions north to south and west to east. Each plot has an area of approximately one hectare with 3.0 m x 3.7 m spacing. The direction of planting row was not differed each other for both growth rate and survival. In the early growth up to 8 years old, diameter and height growth tends to be increase with number of row from type A to type E, except for tree height of type E, as a result of low inter-specific competition. At the age of 16 years old, S. leprosula was almost dominant in all planting designs of multi-storied forest and replacing the exotic species of A. mangium. The competition for both inter- and intra-specific was high as depicted by survival rate which decreased with increasing number of row from type B to type E as well as mean annual increment. The best performance of tree growth was type C, which is four rows of S. leprosula and four rows of A. mangium with 21.99 cm, 20.09 m and 66.4% of average diameter, total height and survival rate, respectively. The volume of best planting design was 152.23 m3 ha-1 and the total biomass was 79.42 tonnes ha-1 (≈ 34.76 tonnes net C ha-1), 59.62 tonnes ha-1 of aboveground biomass and 19.80 tonnes ha-1 of root biomass. The best planting design can absorp 124.97 tonnes net CO2. The type C of planting design is recommended for optimum growth performance, stand productivity and capacity of CO2 absorption in multi-stored forest management.The study was also derived specific equations (tier 3) and carbon content at different tree component and tree age through destructive sampling method. Biomass proportion were 56.88, 14.92, 3.48, and 24.85% for stem, branches, leaves and root, while average carbon content were 43.77, 42.63, 43.55 and 41.02%, respectively. Shorea leprosula or called light red meranti was sound to be one of the promising species for reforestation as well as for replacing exotic species, however, this species has irregular pattern of flowering and short period of seed storage. Thus, vegetative propagule offers a feasible solution for seedling production. Data on vegetative propagule performance in the field is very limited and this has to be tested before recommended for large scale plantation establishment. In particular, no biomass studies have been done in the trees from stem cuttings. The evaluation of potential production and biomass accumulation of 12-y old S. leprosula cuttings was carried out in Gunung Dahu Forest Research, West Java, Indonesia. Based on basal area distribution, destructive samplings of 18 representative trees in different spacing and planting types were also done. The results showed that the diameter and height growth and the proportion of canopy were found to have positive relationship with spacing regime except survival rate which was found to have negative relationship. Growth performance of this species in monoculture planted-system showed better results than the other in mix planted-system with pines for all spacing regimes, while the proportion of canopy was not different to each other. The regression models related to growth parameters, such as diameter (D) and total height (H) to stem volume and biomass of tree component or combination of tree component were constructed. These models were then used to estimate stem and biomass accumulation for all stands. Production potential of 12-yr-old Shorea leprosula from stem cuttings are 154.85, 136.97, 38.95 and 83.22, 72.99, 48.41 m3/ha for monoculture planted of 2 x 2, 3 x 3, 5 x 5 and mix planted with pine of 2 x 2, 3 x 3 and 5 x 5 m spacing, respectively and their total biomass accumulations are 89.89, 76.78, 24.27 and 49.74, 43.95, 30.05 ton/ha. Based on study 4, individual trees responded to wider spacing and lower competition resulted greater individual production and biomass accumulation as well as diameter growth, which monoculture planting system tends to be higher in productivity than mix-planting system. The figure for production potential and biomass accumulation indicate that their quantifications can be estimated using only D and combination D-H for both specific and a stand equations. Since forest productivity seems to be affected by suitable of species to site condition and planting technique, spacing, planting type, planting design and application of organic materials should be considered to ensure sustainability in producing high productivity and for future forest rehabilitation and restoration. Based on study 1 to 4, data of forest inventories tend to be highly variable, especially in very diverse mosaic landscapes, in different forest-type and different silviculture treatments. The study has demonstrated the tested general allometric relationships are not as accurates forest type-specific allometric equation. Thus, converting forest inventory into volume, biomass and carbon of dipterocarp forest of Southeast Asia requires the development of specific allometric relationships (study 5). For this purpose, data were collected from several sites in Southeast Asia, both from man-made forests and natural forests. Trees sampled from man-made forests were smaller than 30 cm in diameter and chosen based on diameter distribution, while trees sampled from natural forest were bigger than 20 cm in diameter and chosen depending on normality of tree structure during operational felling activities of logging companies. In total, 119 sample trees with D ranging from 1.2 cm to 114.6 cm and H ranging from 1.9 m to 59.1 m were destructively. Examination of the model residuals of the forest type-specific equation (model A) indicated that using D alone as the predictor variable produced stable relationship, but the inclusion of H as a second predictor variable increased the performance of the model, both for stem volume and biomass. Biomass expansion factor was decreased with increasing D from 1.6 for D less than 10 cm to 1.2 for D more than 40 cm. The study have therefore compared with several general allometric equations resulted that general equations are not as accurate as forest type-specific equationfor estimating biomass in the dipterocarp forest of Southeast Asia. The forest-type allometric equation is recommended for use in the estimation of biomass and stem volume from inventory measurements. Therefore, using the equations, how much emission can be reduced from the REDD project and/or how much CO2 can be absorbed from A/R and IFM project can be estimated more accurately and verifiable.